Odpowiedź :
[tex]1)\\\\2(x-3)-(x+5)=3(x+1)-2(x-3)\\\\2 x-6- x-5=3 x+3-2 x+6\\\\x-11=x+9\\\\x-x=9+11\\\\0=20\\\\sprzeczne,\ brak\ rozwiazania[/tex]
[tex]2)\\\\4(x+1)-7=2(2x+3)-9\\\\4 x+4-7=4x+6-9\\\\4x-3=4x-3\\\\nieoznaczone ,\ nieskonczenie\ wiele\ rozwiazan[/tex]
[tex]3)\\\\ 4x-(2x+3)=5(x+2)-3(x+3)\\\\4x- 2x-3=5 x+10-3 x-9\\\\2x-3=2x+1\\\\2x-2x=1+3\\\\0=4\\\\sprzeczne,\ brak\ rozwiazania[/tex]
[tex]4)\\\\3x-(x-5)=4(x-3)-3(2x-5)\\\\3x- x+5 =4 x-12-6 x+15\\\\2x+5=-2x+3\\\\2x+2x=3-5\\\\4x=-2\ \ |:4\\\\x=-\frac{2}{4}\\\\x=-\frac{1}{2}[/tex]
[tex]5)\\\\ 5x+(x-3)=3(x+2)+(3x-9)\\\\ 5x+ x-3 =3 x+6+ 3x-9 \\\\6x-3=6x-3\\\\rownanie\ nieoznaczone\ nieskonczenie\ wiele\ rozwiazan[/tex]
[tex]6)\\\\ 3x+2(2x-4)=5(2x-1)-(3x+3)\\\\3x+4x-8=10x-5- 3x-3\\\\7x-8=7x-8 \\\\rownanie\ nieoznaczone\ nieskonczenie\ wiele\ rozwiazan[/tex]
[tex]7)\\\\2x+3(x+1)=4x+(x+2)+1\\\\ 2x+3 x+3 =4x+ x+2 +1\\\\5x+3=5x+3 \\\\rownanie\ nieoznaczone\ nieskonczenie\ wiele\ rozwiazan[/tex]